2021
DOI: 10.3390/v13112109
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Virus-Infected Cells with Soft X-ray Tomography

Abstract: Viruses are obligate parasites that depend on a host cell for replication and survival. Consequently, to fully understand the viral processes involved in infection and replication, it is fundamental to study them in the cellular context. Often, viral infections induce significant changes in the subcellular organization of the host cell due to the formation of viral factories, alteration of cell cytoskeleton and/or budding of newly formed particles. Accurate 3D mapping of organelle reorganization in infected ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…To further characterise the intracellular environment of patient-derived fibroblasts, we used cryo-soft X-ray tomography (Cryo-SXT). This synchrotron-based technique uses soft X-rays to image samples in the water-window energy absorption range (520 eV) [ 23 , 24 ]. Cryo-SXT is the only available imaging technique that can yield nanometer-resolution 3D maps from vitrified whole-cell samples (thus avoiding chemical treatment or sectioning of the sample and the potential artefacts that come with these treatments).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further characterise the intracellular environment of patient-derived fibroblasts, we used cryo-soft X-ray tomography (Cryo-SXT). This synchrotron-based technique uses soft X-rays to image samples in the water-window energy absorption range (520 eV) [ 23 , 24 ]. Cryo-SXT is the only available imaging technique that can yield nanometer-resolution 3D maps from vitrified whole-cell samples (thus avoiding chemical treatment or sectioning of the sample and the potential artefacts that come with these treatments).…”
Section: Resultsmentioning
confidence: 99%
“…Anatomically, collagen VI is distributed in the stromal interface surrounding interstitial cells in proximity to the basement membrane [ 3 ]. Once secreted in the extracellular space, tetramers associate end-to-end forming microfibrils that create a network able to maintain skeletal muscle function and integrity and allow a proper link between muscle cells and the extracellular matrix (ECM) [ 12 , 13 , 23 ]. Importantly, the Gly293Arg substitution introduces folds/kinks that prevent proper assembly with other tetramers to form collagen VI microfibrils [ 8 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 4–10 ] Because of these unique characteristics, SXT has been recently used in a wide range of applications, from phenotyping of cells such as bacteria, yeast, and advanced eukaryotes [ 11–16 ] to investigating cell–nanoparticle, [ 17,18 ] cell–parasite, [ 19–21 ] and cell–virus interactions. [ 22–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Because of these unique characteristics, SXT has been recently used in a wide range of applications, from phenotyping of cells such as bacteria, yeast, and advanced eukaryotes [11][12][13][14][15][16] to investigating cellnanoparticle, [17,18] cell-parasite, [19][20][21] and cell-virus interactions. [22][23][24][25][26][27][28] SXT is suitable for imaging of a wide variety of cell types. However, some investigators have reported that soft X-ray imaging is limited to specimens less than 10 μm thick.…”
Section: Introductionmentioning
confidence: 99%
“…Among existing structural imaging modalities for cell biology, soft x-ray tomography (SXT) uniquely enables whole-cell imaging with a few tens of nanometers spatial resolution, minimal sample preparation, and quantitative contrast of protein-rich intracellular structures [4][5][6][7][8][9][10] . Due to these unique characteristics, SXT recently has been used for a wide range of applications, from phenotyping of cells such as bacteria, yeast, and advanced eukaryotes [11][12][13][14][15][16] to investigating cell-nanoparticle 17,18 , cell-parasite [19][20][21] and cellvirus interactions [22][23][24][25][26][27] .…”
mentioning
confidence: 99%